2021
DOI: 10.1002/cncr.34056
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and spectrum of pathogenic variants among patients with multiple primary cancers evaluated by clinical characteristics

Abstract: Background Multiple primary cancers (MPCs) are a hallmark of cancer predisposition syndromes. Here the frequency of germline pathogenic variants (PVs) among patients with MPCs is reported. Methods Patients with MPCs who underwent multigene panel testing from March 2012 to December 2016 were studied. Eligible patients had an analysis of 21 genes: ATM, BARD1, BRCA1, BRCA2, BRIP1, CDH1, CHEK2, EPCAM, MLH1, MSH2, MSH6, MUTYH, NBN, NF1, PALB2, PMS2, PTEN, RAD51C, RAD51D, STK11, and TP53. The frequencies of PVs by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…While we have found eight PV carriers in HBOC genes and four carriers in LS genes (including a patient with co-occurrence of BRCA1 and MLH1 PV and diagnosed with EC, OC, and BC) in the group of 69 patients with EC and OC (11.6%), we have identified eight carriers of LS genes mutation and only one additional carrier of the CHEK2 gene mutation (a patient with EC, CRC, and melanoma) in the group of 34 patients with EC and CRC (26.5%). This suggests that the presence of double primary tumors could potentially represent a sole indication criterion for germline genetic testing, as indicated by previous studies ( 19 , 20 , 35 , 36 ).…”
Section: Discussionsupporting
confidence: 64%
“…While we have found eight PV carriers in HBOC genes and four carriers in LS genes (including a patient with co-occurrence of BRCA1 and MLH1 PV and diagnosed with EC, OC, and BC) in the group of 69 patients with EC and OC (11.6%), we have identified eight carriers of LS genes mutation and only one additional carrier of the CHEK2 gene mutation (a patient with EC, CRC, and melanoma) in the group of 34 patients with EC and CRC (26.5%). This suggests that the presence of double primary tumors could potentially represent a sole indication criterion for germline genetic testing, as indicated by previous studies ( 19 , 20 , 35 , 36 ).…”
Section: Discussionsupporting
confidence: 64%
“… 18 , 19 Bychkovsky et al’s analysis on 9714 multiple primary cancer patients showed the prevalence of germline pathogenic variants increased with the number of primary cancers (PCs): 13.1% with 2 PCs, 15.9% with 3 PCs, and 18.0% with ⩾4 PCs ( P = .00056). 20 In Win et al’s study over an average follow-up duration of 5 years, people with mismatch repair had an increased risk of colorectal cancer, bladder cancer, and urinary tract cancer. 21 Lynch syndrome (LS) is also a high-risk factor for multiple primary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of gHR mut in our cohort was 9.7% (51/527), which is in line with the results of previous reports (9.7–16.5%) [ 32 , 50 52 ]. The incidence of gHR mut in current study might be underestimated because patients with multiple primary cancers, who were more likely to harbor germline cancer susceptibility gene mutations, were excluded from initial study [ 53 ].…”
Section: Discussionmentioning
confidence: 99%